1977
DOI: 10.1163/26660644-04602014
|View full text |Cite
|
Sign up to set email alerts
|

Deilagaon, a New Genus of Indo-Malayan and Papuan Fig Wasps (Hymenoptera, Chalcidoidea, Agaonidae)

Abstract: Introduction of the new genus Deilagaon with descriptions of new species chrysolepidis (type-species) from the Philippines (type-locality Luzon, ex Ficus chrysolepis Miq.), Celebes, New Guinea (ex F. novoguineensis Corner), Bismarck Archipelago, Solomon Isis.; and annulatae from Thailand, Malaya (ex F.depressa Bl.), Sumatra, Borneo (type-locality N. Borneo, ex F. annulata Bl.), Philippines. Included is also Ceratosolen megarhopalus Grandi (1923) from Thailand, Malaya, Sumatra, Java, Borneo, Philippines (Balaba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 0 publications
0
20
0
2
Order By: Relevance
“…Pleistodontes froggatti –Grandi, 1916b: 150–159 (redescription female and male); Pemberton, 1921: 297–319 (biological notes); Muir, 1922: 12 (introduction into Hawaii); Swezey, 1923: 304; Timberlake, 1924: 419 (Honolulu and Waimea); Swezey, 1925: 372 (introduction into Hawaii); Timberlake, 1927: 552; Girault, 1927: 338, Cairns (female taken at light); Grandi, 1928b: 200 (type specimen examined); Lyon, 1929: 83–97; Pemberton, 1934: 379; Sakimura & Linsford, 1940: 454; Wiebes, 1963: 307; Corner, 1965: 25; Wiebes, 1966: 21; Wiebes, 1977b: 213–214; Wiebes, 1977a: 139; Boucek, 1988: 191; McKey, 1989: 665; Wiebes, 1990: 224; Wiebes, 1991: 141 (several localities from Queensland, Western Australia and New South Wales); Wiebes, 1994b: 26–27.…”
Section: Descriptions Of the Speciesmentioning
confidence: 99%
See 2 more Smart Citations
“…Pleistodontes froggatti –Grandi, 1916b: 150–159 (redescription female and male); Pemberton, 1921: 297–319 (biological notes); Muir, 1922: 12 (introduction into Hawaii); Swezey, 1923: 304; Timberlake, 1924: 419 (Honolulu and Waimea); Swezey, 1925: 372 (introduction into Hawaii); Timberlake, 1927: 552; Girault, 1927: 338, Cairns (female taken at light); Grandi, 1928b: 200 (type specimen examined); Lyon, 1929: 83–97; Pemberton, 1934: 379; Sakimura & Linsford, 1940: 454; Wiebes, 1963: 307; Corner, 1965: 25; Wiebes, 1966: 21; Wiebes, 1977b: 213–214; Wiebes, 1977a: 139; Boucek, 1988: 191; McKey, 1989: 665; Wiebes, 1990: 224; Wiebes, 1991: 141 (several localities from Queensland, Western Australia and New South Wales); Wiebes, 1994b: 26–27.…”
Section: Descriptions Of the Speciesmentioning
confidence: 99%
“…ex Vent.) are considered to be, respectively, the same as P. froggatti (Wiebes, 1977a: 140) and P. imperialis but were never formally synonymized. Pleistodontes liszti Girault, 1932, a species still unrecognized, and Pleistodontes medionigra (Girault, 1933), transferred by Hill (1967a: 92) to Pleistodontes , are both considered to be the same as P. imperialis (Boucek, 1988) but are not formally synonymized.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Waterstoniella and Deilagaon. Deilagaon has been allied historically to Waterstoniella on the basis of morphological evidences (Wiebes, 1977). Indeed, Deilagaon differs from Waterstoniella only by its club‐shaped antennae bearing numerous sensillae, but otherwise appears closely related.…”
mentioning
confidence: 99%
“…nov. 3). As pale wasp species are attracted to light at night (see 7679 for the Agaonidae and [21] for the Sycoecinae), we could hypothesize that the first species exploit pools of F. chirindensis figs attractive at night whereas the dark species exploit pools of figs attractive at day. It has been shown that co-occuring agaonid species may have different longevity and ability to resist desiccation [80].…”
Section: Discussionmentioning
confidence: 99%